Deformation control during the laser welding of a Ti6Al4V thin plate using a synchronous gas cooling method. (15th January 2016) - Zhang, Yi; Ying, Yeyong; Liu, Xixia; Wei, Haiying
Abstract: To reduce longitudinal flexural deformations during the laser welding of Ti6Al4V thin plates, this paper presents a synchronous gas cooling method (SGCM) that uses liquid nitrogen-cooled argon gas with the laser source to actively control the cooling process during welding. Compared to the conventional welding, the dimension of the fusion zone (FZ) obtained with SGCM welding is the same, while the prior β grains and the acicular α′ phase for the SGCM become fine on the morphology. In the heat affected zone (HAZ), the dimension on the SGCM condition is smaller than that for the conventional welding. Furthermore, an SGCM laser welding model is developed. Simulations of the traditional laser welding process and the welding process with the SGCM show that the synchronous gas cooling affects the longitudinal flexural deformation and the longitudinal residual stress. The simulation results are verified by experiments, which show that a 71% reduction in deformation, a 21% reduction in longitudinal residual stress and a 14% reduction in longitudinal plastic strain is achieved with this method. Graphical abstract: Highlights: A synchronous gas cooling method is proposed to control laser welding deformation. A model is developed for the method and is verified by laser welding experiments. A 71% reduction in welding deformation is achieved with the method. Heat sink with the cooled argon leads to fine grains in the fusion zone.